Cognitive and psychosocial function in retired professional hockey players. Issue 6 (10th April 2017) - Esopenko, Carrie; Chow, Tiffany W; Tartaglia, Maria Carmela; Bacopulos, Agnes; Kumar, Priya; Binns, Malcolm A; Kennedy, James L; Müller, Daniel J; Levine, Brian
Abstract : Background and Objective: The relationship between repeated concussions and neurodegenerative disease has received significant attention, particularly research in postmortem samples. Our objective was to characterise retired professional ice hockey players' cognitive and psychosocial functioning in relation to concussion exposure and apolipoprotein ε4 status. Methods: Alumni athletes (N=33, aged 34–71 years) and an age-matched sample of comparison participants (N=18) were administered measures of cognitive function and questionnaires concerning psychosocial and psychiatric functioning. Results: No significant group differences were found on neuropsychological measures of speeded attention, verbal memory or visuospatial functions, nor were significant differences observed on computerised measures of response speed, inhibitory control and visuospatial problem solving. Reliable group differences in cognitive performance were observed on tests of executive and intellectual function; performance on these measures was associated with concussion exposure. Group differences were observed for cognitive, affective and behavioural impairment on psychosocial questionnaires and psychiatric diagnoses. There was no evidence of differential effects associated with age in the alumni athletes. Possession of an apolipoprotein ε4 allele was associated with increased endorsement of psychiatric complaints, but not with objective cognitive performance. Conclusions: We found only subtle objective cognitive impairment in alumni athletes in the context of high subjective complaints and psychiatric impairment. Apolipoprotein ε4 status related to psychiatric, but not cognitive status. These findings provide benchmarks for the degree of cognitive and behavioural impairment in retired professional athletes and a point of comparison for future neuroimaging and longitudinal studies.